Pharmacoeconomic analysis of rituximab and belimumab therapy in patients with systemic lupus erythematosus - D. A. Gerasimova; V. A. Gontarenko; E. V. Gerasimova; O. V. Zakharova; L. А. Lobuteva; T. V. Popkova; A. M. Lila (Современная ревматология, 2024)
The progressive course of systemic lupus erythematosus (SLE) with high activity and severe internal organs involvement requires the prescription of expensive biologic disease-modifying antirheumatic drugs (bDMARDs), rituximab (RTM) and belimumab (BLM), whose comparative clinical and economic efficacy has not been adequately studied.Objective: to evaluate the clinical and economic efficacy of RTM and BLM therapy in patients with SLE.Material and methods. The study included 50 SLE patients who were divided into two groups and received RTM (group 1, n=25) or BLM (group 2, n=25) therapy for 12 months. The clinical and economic analysis was performed with the cost-effectiveness method using the cost-per-responder (CPR) model. A clinically significant improvement in SLEDAI-2K (Systemic Lupus Erythematosus Disease Activity Index modified 2K; Δ ≥4) was considered a response to therapy. Direct and indirect costs were considered in the analysis.Results and discussion. Against a background of therapy, there was a decrease in SLE activity with a decrease in median SLEDAI-2K in group 1 from 12 [10.5; 18] to 8 [4; 10] and in group 2 from 10 [8; 14.5] to 4 [2; 4] (p< 0.001 in both cases). A clinically significant improvement was observed in 56% of patients in group 1 and 72% of patients in group 2. The peculiarities of the BLM dosing regimen caused higher (1.7 times) total costs than in the case of RTM. According to the CPR value, RTM showed a greater benefit (1.3 times) than BLM (954 thousand rubles versus 1.25 million rubles). The incremental cost-effectiveness ratio (ICER) was 1.4 million rubles, which does not exceed the threshold of willingness to pay for a domestic patient.Conclusion. When comparing BLM and RTM therapy for SLE patients in real-life clinical practice, greater clinical and economic efficiency was demonstrated for RTM. BLM therapy was found to be “cost-effective”.